2021
DOI: 10.1158/1078-0432.ccr-21-2291
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Copy-Number Alteration Analysis in Plasma Cell-Free DNA of Neuroendocrine Neoplasms is a Novel Specific Biomarker for Diagnosis, Prognosis, and Follow-up

Abstract: Purpose: As noninvasive biomarkers are an important unmet need for neuroendocrine neoplasms (NEN), biomarker potential of genome-wide molecular profiling of plasma cell-free DNA (cfDNA) was prospectively studied in patients with NEN. Experimental Design: Longitudinal plasma samples were collected from patients with well-differentiated, metastatic gastroenteropancreatic and lung NEN. cfDNA was subjected to shallow whole-genome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…It has been reported that the presence of ctDNA in body fluids is linked to the localization of the primary tumor and metastatic lesions [ 129 , 130 , 131 , 132 ]. Oversoe et al described elevated levels of cfDNA in panNET and siNET patients compared to healthy controls [ 133 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the presence of ctDNA in body fluids is linked to the localization of the primary tumor and metastatic lesions [ 129 , 130 , 131 , 132 ]. Oversoe et al described elevated levels of cfDNA in panNET and siNET patients compared to healthy controls [ 133 ].…”
Section: Discussionmentioning
confidence: 99%
“…Boons et al, described a correlation between the presence of ctDNA and a higher grading [ 132 ]. On the contrary to NECs, NETs (which are generally slow growing tumors) have a lower cell loss index and ctDNA release and can often be ctDNA negative [ 130 ]. Quantitative analysis of ctDNA may also be useful to assess tumor volume and in an early diagnosis of relapse after surgery and as a predictive factor of response to treatment [ 134 , 135 , 136 , 137 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade there has been a steadily increasing need for the identification of predictive/prognostic factors in all stages of the management of panNEN/NEN patients with advanced disease [ 7 , 383 , 384 , 385 ]. This has occurred for a number of reasons, but is largely related to the increasing complexity of treating these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although not evaluated in the setting of PRRT to date, the presence and increased fractions of circulating tumor DNA were associated with poorer PFS. 48 Further work using circulating tumor cells and DNA may add additional value in understanding who will benefit the most from PRRT.…”
Section: Developing Role Of Circulating Biomarkersmentioning
confidence: 99%